Utilization of oil palm co-products as feeds for livestock in Malaysia - Wan Zahari Mohamed; A.R. Alimon; H.K. Wong (FAO Publications, Rome, Italy, 2012)
Several oil palm industry co-products can be utilized as animal feed, notably oil palm fronds(OPF), oil palm trunks (OPT), palm press fible(PPF), empty fruit bunches(EFB), palm kernel cake(PKC) and palm oil mill effluent(POME).These co-products are obtained either during the harvesting of the fruits, or the extraction and refining of crude palm oil(CPO) or palm kernel oil(PKO). Many of the co-products from the plantation(field residues) and processing mills need further processing before they can be used effectively in livestock diets.Information on chemical composition, nutritive values, improvement methods and feeding response of ruminants fed oil-palm co-product-based diets are widely documented. Besides livestock feeds, some co-products are also utilized in the manufacturing of industrial products and organic fertilizers.OPF has been successfully utilized as feedstuffs either freshly chopped, as silage, or processed into pellents and cubes. Optimum inclusion level in beef and dairy animals is about 30 percent. Ensiled OPT produced reasonably good liveweight gain(LWG)of about 0.7 kg/day in beef cattle when fed at levels between 30 and 40 percent. PPF has a lower digestibility, which limits its inclusion in ruminant diets to less than 20 percent. PKC is a high-energy source and is a cost-effective ingredient in ration formulations for various livestock species. Beef and dairy production utilizing PKC-based diets are more economical under local dietary and management systems than non-PKS-based diets. High content of fibre and shell can limit use in poultry and aquaculture. With biotechnological treatments, inclusion levels of PKC can be increased to 30 percent for poultry feeding. POME, the residue left from the purification of CPO, can be combined with PKC and OPF to provide a cost-effective and complete ration for feeding ruminant livestock. The use of EFB, the material remaining of fruit bunches after steaming, is very limited and is generally utilized only after irradiation and culture-substrate treatments. The utilization of other locally available oil-palm-based co-products is targeted at increasing dietary energy content and improving nutrient digestibility. These include palm-fatty acid distillates(PFAD)and CPO, which are more suited for supplementing dairy animals, poultry, swine and aquaculture. The use of spent bleaching earth(SBE), another co-product from the oil-palm refineries, is very limited at present.Improvement in feed conversion efficiency(FCE)and maximizing the use of local feedstuffs represents a potential area of application to reduce the high cost of feed in Malaysia, especially in the non-ruminant subsector.